Development of Health Integrative Thematic Textbooks (Batik) To Provide Health Education in Elementary Schools - I Ketut Sudiana; N. Adiputra; Putu Budi Adnyana (Jurnal Pendidikan Indonesia, 2019)
This research aims to develop health integrative thematic textbooks (BATIK). The method used is the Research and Development model of Borg & Gall. Based on the research, it obtained that integrated health education material in accordance with the PHBS indicator of school. Integration using two patterns, explicitly through the subtitle "Ayo Lakukan Hidup Bersih dan Sehat", and implicitly integrated into the text, the use of children's songs and illustrated images that contain of health education. The BATIK assessment at the validation and readability stage obtained the following results: (1) validation by experts obtained very good, (2) validation by elementary school teachers obtained very good, (3) a one to one evaluation readability test obtained good, and (4) a small group evaluation readability test obtained very good. Based on the results of the validation and readability test, it shows that the quality of BATIK is good so it is suitable to be used in thematic learning in elementary schools.